Geotechnical aspects of underground construction in soft ground : proceedings of the Tenth International Symposium on Geotechnical Aspects of Underground Construction in Soft Grounds IS-Cambridge 2022, Cambridge, United Kingdom, 27-29 June 2022 /: proceedings of the Tenth International Symposium on Geotechnical Aspects of Underground Construction in Soft Grounds IS-Cambridge 2022, Cambridge, United Kingdom, 27-29 June 2022. (2021) - Unknown
No abstract available